A Portable Solar-Powered Wireless Charger: Design, Implementation, and Performance Analysis - Alfarid Hendro Yuwono; Deshinta Arrova Dewi; Rajani Balakrishnan; Reza Rahmadian; Nafi Isbadrianingtyas; Widi Aribowo; Vugar Hacimahmud Abdullayev; Aliyu Sabo (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
The increasing demand for portable and off-grid charging solutions has motivated the development of solar-powered wireless power transfer (WPT) systems for consumer electronics. This paper presents the design, implementation, and experimental performance evaluation of a portable solar-powered wireless charger that integrates a 3-Wp photovoltaic (PV) panel with a near-field inductive coupling WPT system operating at a resonant frequency of 90 kHz. The research contribution is a fully integrated, low-cost prototype that demonstrates the feasibility of combining solar energy harvesting with contactless inductive charging for mobile devices, addressing the gap in portable off-grid wireless charging solutions. The system comprises a solar panel connected to a powerbank serving as an energy buffer, a series-series (SS) compensated inductive coil pair, a high-frequency inverter, and an AC/DC rectifier stage. Experimental testing was conducted in Malang City, Indonesia, under natural sunlight conditions. Results showed that the solar panel output voltage ranged from 6.2 V to 6.8 V under direct sunlight, declining by more than 30% under cloudy conditions. Peak power transfer efficiency of 65.3% was achieved at the 90 kHz resonant frequency, and efficiency decreased inversely with coil separation distance, dropping from 65.3% at 0 cm to below 10% at 5 cm. The powerbank required approximately 460 minutes of solar charging to reach 4 V, and the mobile phone battery charged at an average rate of 8.5 minutes per 1% capacity increase, compared to approximately 4.2 minutes per 1% for a standard wired charger. The study demonstrates the practical feasibility of portable solar-WPT integration for outdoor and emergency charging applications, while identifying weather dependence and limited effective coil distance as primary constraints for future optimization. This research aligns with the United Nations Sustainable Development Goals (SDGs), particularly SDG 7 (Affordable and Clean Energy) by promoting renewable energy access and photovoltaic technology for off-grid communities, SDG 9 (Industry, Innovation and Infrastructure) through the development of innovative low-cost wireless charging infrastructure, SDG 11 (Sustainable Cities and Communities) by enabling resilient and portable energy solutions for underserved and emergency settings, and SDG 13 (Climate Action) by advancing clean energy alternatives that reduce dependence on fossil-fuel-based electricity.